What is the value of this expression when a=3 and b= -2? (3a (exponent) -2 b (exponent) 6) exp. -2 ___________________________ (2a (exponent) -1 b (exponent) 5) Its all one equation!

Respuesta :

Answer:

I looked online to find the equation well written, but i could not find it, so i will guess that the equation is:

[tex]\frac{3*a^{-2} - 2*b^{-6}*e^{-2}}{2*a^{-1}*b^{5}}[/tex]

Now we want to find the value of this equation when:

a = 3 and b = -2

So we can just replace these values in the equation, each a is replaced by a 3, and each b is replaced by a -2.

The equation becomes.

[tex]\frac{3*3^{-2} - 2*(-2)^{-6}*e^{-2}}{2*3^{-1}*(-2)^{5}} = 44.3[/tex]

ACCESS MORE